Using Extending Concept through Language Activities (ECOLA) Technique to Improve Students’ Reading Comprehension Skill - Pratama, Riyadi; Wagiyo, Supiah; Rahman, Priyanggo Karunia (English Education Department, 2022)
The objective of this study was to find out whether there is a significant difference in students’ reading comprehension between the experimental and the control group. The sample of this study were taken from two classes of the second year of a private high school in Bangka Belitung province. This study is an experimental study with quasi-experimental design. The data were collected through Observation and Test. They were then analyzed by using T-Test.The result showed that the rxy (17.16) was higher compared to rtable at significant level (0.432). Thus, the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. Furthermore, there was a significant difference between students’ reading skill of the experimental class and those of the control one. In conclusion, the students’ reading comprehension in narrative text has been improved by using Extending Concept through Language Activities.